Advanced Nail Surgery - Haneke, Eckart (Medknow Publications & Media Pvt Ltd, 2011)
Six techniques not yet widely known or used in the dermatologic surgery of the nails are briefly described. Small-to-medium-sized tumours of the proximal nail fold (PNF) can be excised and the defect repaired with advancement or rotation flaps. A superficial biopsy technique of the matrix for the diagnosis of longitudinal brown streaks in the nail, which allows rapid histological diagnosis of the melanocyte focus to be performed, is described here. Because the excision is very shallow and leaves the morphogenetic connective tissue of the matrix intact, the defect heals without scarring. Laterally positioned nail tumours can be excised in the manner of a wide lateral longitudinal nail biopsy. The defect repair is performed with a bipedicled flap from the lateral aspect of the distal phalanx. Malignant tumours of the nail organ often require its complete ablation. These defects can be covered by a full-thickness skin graft, reversed dermal graft, or cross-finger flap. The surgical correction of a split nail is often difficult. The cicatricial tissue of the matrix and PNF have to be excised and the re-attachment of these wounds prevented. The matrix defect has to be excised and sutured or covered with a free matrix graft taken either from the neighbouring area or from the big toe nail.